2009
DOI: 10.1111/j.1365-2222.2008.03133.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic supplementation in the first 6 months of life in at risk Asian infants – effects on eczema and atopic sensitization at the age of 1 year

Abstract: Early life administration of a cow's milk formula supplemented with probiotics showed no effect on prevention of eczema or allergen sensitization in the first year of life in Asian infants at risk of allergic disease. Further work is needed to determine whether timing of supplementation, dose and probiotic strain are important considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(133 citation statements)
references
References 36 publications
3
125
1
3
Order By: Relevance
“…Infants receiving L rhamnosus HN001 had a significantly lower risk of eczema than infants receiving placebo, but this was not the case for B animalis subsp lactis and there was no significant effect of these two strains on atopy (Wickens et al, 2008). Taylor et al ( 2006a;2007a;2007b) and of Soh et al (2009) studied newborns given, from birth to 6 months of life, L. acidophilus LAVRI-A1 (178 infants) and a mixture of L. rhamnosus LPR and B. longum BL999 (253 infants), respectively, and did not find any reduction of the risk of AD in high-risk infants as assessed from the numbers of patients affected, SCORAD score or IgE sensitization. Moreover, L. acidophilus was associated with increased allergen sensitization (Taylor et al, 2007a).…”
Section: Probiotics In the Primary Prevention Of Allergic Diseasesmentioning
confidence: 82%
“…Infants receiving L rhamnosus HN001 had a significantly lower risk of eczema than infants receiving placebo, but this was not the case for B animalis subsp lactis and there was no significant effect of these two strains on atopy (Wickens et al, 2008). Taylor et al ( 2006a;2007a;2007b) and of Soh et al (2009) studied newborns given, from birth to 6 months of life, L. acidophilus LAVRI-A1 (178 infants) and a mixture of L. rhamnosus LPR and B. longum BL999 (253 infants), respectively, and did not find any reduction of the risk of AD in high-risk infants as assessed from the numbers of patients affected, SCORAD score or IgE sensitization. Moreover, L. acidophilus was associated with increased allergen sensitization (Taylor et al, 2007a).…”
Section: Probiotics In the Primary Prevention Of Allergic Diseasesmentioning
confidence: 82%
“…Probiotic supplementation to the mother during pregnancy, as well as to her baby postnatally, may be important for preventive effects on childhood allergic disease [55]. Thus, a preventive effect on atopic eczema, the most common allergic disease at this age, has primarily been demonstrated in studies where probiotics were given both pre-and postnatally [48,49,[56][57][58][59], whereas two studies with postnatal supplementation only failed to prevent allergic disease [60,61].…”
Section: Probiotics In Human Allergy Prevention Trialsmentioning
confidence: 99%
“…4 NO. 18 We found five studies including 191 patients that reported deaths as a result of SCC, 547,585,[588][589][590] with an average of 9.1% of patients dying from their disease on pooled analysis (95% CI 1.4% to 22.8%; I 2 = 79%) 23,67,[70][71][72] ( Figure 43). The greatest proportion of deaths was observed in a study of advanced T4 tumours in which two of three patients with eligible SCCs died (66%, 95% CI 9.4% to 99.1%) 590 during a mean follow-up period of 14 months.…”
Section: Squamous Cell Skin Cancer Work Programmementioning
confidence: 99%
“…early, late and prolonged formula feeding; exclusively breastfed, mixed breastfed or exclusively formula-fed; and high or normal risk for allergic disease) which makes it difficult to perform meta-analyses in such populations. Trials of prebiotic and probiotic interventions also suffered from large heterogeneity in the interventions and it should be noted that several probiotic trials have been published since the last systematic review on this subject, [62][63][64][65][66][67][68][69][70] warranting an updated review.…”
Section: Quality Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation